Die Anämie bei malignen Tumorerkrankungen - Aulbert, E. (Nuklearmedizin - NuclearMedicine, 1989)
The cellular uptake and lysosomal accumulation of 67Ga-labelled transferrin within tumors of different malignancy were examined using tissue fractionation and immunological techniques. As tumor models the slowly growing Morris hepatoma 5123C, the moderately growing Novikoff hepatoma and the fast and aggressive Yoshida hepatoma AH 130 were investigated. Isolation of subcellular fractions of tumor homogenates was performed by differential centrifugation and density-gradient centrifugation. The intracellular 67Gatransferrin was found to be highly concentrated within the purified lysosomes. The transferrin within the lysosomal fraction was identified by radial immunodiffusion technique using monospecific antiserum. The accumulation of 67Gatransferrin by the tumors resulted in a faster disappearance of 67Ga-transferrin from the blood. This loss of circulating 67Ga-transferrin correlated with the proliferation activity and the spread of the tumors. Since transferrin is indispensible for the utilization of iron by the heme-synthesizing red cell precursors, transferrin concentration in the blood is the limiting factor for the utilization of iron in hemoglobin synthesis. Thus, in a further series of experiments we investigated the development of anemia in tumor-bearing rats. With increasing tumor mass a progressive fall of hemoglobin concentration was found. The anemia was more severe in the faster growing Novikoff hepatoma than in the slowly growing Morris hepatoma. The most significant reduction of hemoglobin concentration was found in the very fast growing Yoshida hepatoma. After total tumor resection hemoglobin concentration and red blood cell count normalized completely within 6-8 weeks. We conclude from these data that the uptake of transferrin by the tumor cells results in a faster disappearance of transferrin from the blood. This loss of circulating transferrin correlates with tumor mass and proliferation activity and is one of the factors responsible for the anemia seen in patients with malignant tumors.